Three Novel Rice Genes Closely Related to the ArabidopsisIRX9, IRX9L, and IRX14 Genes and Their Roles in Xylan Biosynthesis - Chiniquy, Dawn; Varanasi, Patanjali; Oh, Taeyun; Harholt, Jesper; Katnelson, Jacob; Singh, Seema; Auer, Manfred; Simmons, Blake; Adams, Paul D.; Scheller, Henrik V.; Ronald, Pamela C. (Frontiers in Plant Science, 2013)
Xylan is the second most abundant polysaccharide on Earth, and represents a major component of both dicot wood and the cell walls of grasses. Much knowledge has been gained from studies of xylan biosynthesis in the model plant, Arabidopsis. In particular, the irregular xylem (irx) mutants, named for their collapsed xylem cells, have been essential in gaining a greater understanding of the genes involved in xylan biosynthesis. In contrast, xylan biosynthesis in grass cell walls is poorly understood. We identified three rice genes Os07g49370 (OsIRX9), Os01g48440 (OsIRX9L), and Os06g47340 (OsIRX14), from glycosyltransferase family 43 as putative orthologs to the putative β-1,4-xylan backbone elongating Arabidopsis IRX9, IRX9L, and IRX14 genes, respectively. We demonstrate that the overexpression of the closely related rice genes, in full or partly complement the two well-characterized Arabidopsis irregular xylem (irx) mutants: irx9 and irx14. Complementation was assessed by measuring dwarfed phenotypes, irregular xylem cells in stem cross sections, xylose content of stems, xylosyltransferase activity of stems, and stem strength. The expression of OsIRX9 in the irx9 mutant resulted in xylosyltransferase activity of stems that was over double that of wild type plants, and the stem strength of this line increased to 124% above that of wild type. Taken together, our results suggest that OsIRX9/OsIRX9L, and OsIRX14, have similar functions to the Arabidopsis IRX9 and IRX14 genes, respectively. Furthermore, our expression data indicate that OsIRX9 and OsIRX9L may function in building the xylan backbone in the secondary and primary cell walls, respectively. Our results provide insight into xylan biosynthesis in rice and how expression of a xylan synthesis gene may be modified to increase stem strength.